Answer:
B
D
A
Step-by-step explanation:
Given:
A. [tex]2x^3-x^{2} -6x[/tex]
B. [tex]2x^3+8x+4[/tex]
C. [tex]3x^4+x^{2} +x-7[/tex]
D. [tex]3x^4-3x^{2} +5x-7[/tex]
Now, let us evaluate the given expressions one by one.
[tex](4x^3-4+ 7x)-(2x^3-x-8)\\\Rightarrow 4x^3-4+ 7x-2x^3+x+8\\\Rightarrow 2x^3+8x+ 4[/tex]
It is equation B.
So, [tex](4x^3-4+ 7x)-(2x^3-x-8)[/tex] is equivalent to B.
[tex](-3x^2+x^4+x)+(2x^4-7+4x)\\\Rightarrow -3x^2+x^4+x+2x^4-7+4x\\\Rightarrow3x^4-3x^{2} +5x-7[/tex]
It is equation D.
So, [tex](-3x^2+x^4+x)+(2x^4-7+4x)[/tex] is equivalent to D.
[tex](x^{2} -2x)(2x+3)\\\Rightarrow 2x^3-4x^{2} +3x^{2} -6x\\\Rightarrow 2x^3-x^{2} -6x[/tex]
It is equation A.
So, [tex](x^{2} -2x)(2x+3)[/tex] is equivalent to A.
So, answer is:
B
D
A